1995
DOI: 10.1093/glycob/5.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Further studies of the binding specificity of the leukocyte adhesion molecule, L-selectin, towards sulphated oligosaccharides—suggestion of a link between the selectin- and the integrin-mediated lymphocyte adhesion systems

Abstract: This communication is concerned with the binding specificity of the leukocyte-adhesion molecule L-selectin (leukocyte homing receptor) towards structurally defined sulphated oligosaccharides of the blood group Le(a) and Le(x) series, and of the glycosaminoglycan series heparin, chondroitin sulphate and keratan sulphate. The recombinant soluble form of the rat L-selectin (L-selectin-IgG Fc chimera) investigated here was shown previously to bind to lipid-linked oligosaccharides 3-O, 4-O and 6-O sulphated at gala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 0 publications
1
42
0
3
Order By: Relevance
“…In accord with this finding is an earlier report that L-selectin binding is abolished by modification of the fucose in the 3Ј-sialyl-Le x sequence by removal of oxygen at position 2, 3, or 5 (18). The presence of the fucose is apparently less critical in the 3Ј-sulfo-Le x sequence as it has been observed that the defucosylated 3Ј-sulfo-Le x tri-and tetrasaccharides are bound by L-selectin, albeit less strongly than the 3Ј-fucosyl analogs (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…In accord with this finding is an earlier report that L-selectin binding is abolished by modification of the fucose in the 3Ј-sialyl-Le x sequence by removal of oxygen at position 2, 3, or 5 (18). The presence of the fucose is apparently less critical in the 3Ј-sulfo-Le x sequence as it has been observed that the defucosylated 3Ј-sulfo-Le x tri-and tetrasaccharides are bound by L-selectin, albeit less strongly than the 3Ј-fucosyl analogs (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…8A). Despite the ability of E-selectin to bind to 3Ј-sulfo-Le X and 3Ј-sulfo-Le a (31,32,55), E-selectin did not bind to 3Ј-sulfolactose or 3Ј,6-disulfolactose and bound only weakly to 3Ј,6Ј-disulfolactose (Fig. 8A).…”
Section: Fig 2 Binding Of L-selectin/igm To Sulfated Lactose Neoglymentioning
confidence: 99%
“…In addition, 3Ј-sulfo Le x inhibits L-selectin-ligand interactions with IC 50 values similar to those of sLe x (34) in static, cell-free binding assays. Moreover, several studies comparing the ability of L-selectin to bind to glycolipid derivatives of 3Ј-sulfo Le x and sLe x indicate that the sulfated derivatives are superior to the corresponding compounds bearing the sialic acid residue (74,75,78), and 3Ј-sulfo Le x -substituted lipids can support L-selectin-mediated rolling (79). Together, these studies suggest that the 3Ј-sulfate substituent can replace the sialic acid residue to afford a mimetic with binding properties similar to sLe x .…”
Section: Monovalent Saccharide Epitopes In Static Bindingmentioning
confidence: 99%